LEARNING STYLES PROFILE AND THEIR IMPACT ON LEARNING BEHAVIOR OF ISLAMIC GUIDANCE AND COUNSELING STUDENTS DURING PANDEMIC - Darmawani, Evia; Suryahadikusumah, Ahmad Rofi (Psikis : Jurnal Psikologi Islami, 2022)
Online learning has followed the learner's modality/learning style. In the context of educational psychology, learning styles have to do with the uniqueness or differences of individuals in learning. Problems that occur when the learning process is not following the learning style are emotional problems, self-efficacy, motivation, etc. This descriptive study aimed to generate a profile of learning styles on research samples, platforms that were often used during online learning, as the trend of learning activities of the samples. Thus, researchers could analyze the relationship between those three variables. The study population and sample were 120 guidance and counseling study program students in the 6th semester. This research used questionnaires as research instruments. The results showed that online learning during the pandemic was not following student learning styles in Islamic guidance and counseling programs, so it had an impact on students’ burnout and learning procrastination. Kinesthetic learning style was the learning style that most respondents had (49.17%). Meanwhile, the learning activity that was often carried out was listening through Zoom meetings. This mismatch had an impact on student interaction, engagement, interests, and motivation. Guidance and counseling courses could emphasize project-based learning activities using the TPACK model. Thus, students could conduct experiments collaboratively with diverse learning styles.